Clinical correlates of human leucocyte antigen (HLA)-G in systemic sclerosis. (10th May 2015) - Favoino, E; Favia, I E; Vettori, S; Vicenti, C; Prete, M; Valentini, G; Perosa, F
Summary: Human leucocyte antigen (HLA)-G has a tolerogenic function and could play a role in the pathogenesis of immune-mediated diseases, including systemic sclerosis (SSc). The aim of this study was to evaluate HLA-G serum expression (sHLA-G) and the HLA-G gene 14 base pairs (bp) insertion/deletion (del − /del + ) polymorphism in patients with Ssc, to search for possible associations with clinical and laboratory variables. sHLA-G was measured by enzyme-linked immunosorbent assay (ELISA) in sera from 77 patients with SSc and 32 healthy donors (HD); the 14 bp del − /del + polymorphism was evaluated by polymerase chain reaction (PCR) amplification of peripheral blood mononuclear cells (PBMC) genomic DNA. Receiver operating characteristics (ROC) analysis identified the HLA-G cut-off that best discriminated dichotomized clinical and serological variables, that was subsequently employed to subdivide SSc patients into HLA-G high (HLA-G + ) and low (HLA-G − ) profile groups. sHLA-G were not statistically different between SSc patients and HD, nor between distinct SSc autoantibody subsets. Subdividing SSc patients by HLA-G positivity or negativity yielded significant differences for the modified Rodnan skin score (mRss) ( P = 0·032), 'general' ( P = 0·031) and 'kidney' ( P = 0·028) Medsger severity scores (MSS) and disease activity index, and especially Δ heart/lung ( P = 0·005). A worse 'general' MSS ( P = 0·002) and Δ heart/lung ( P = 0·011) were more frequent in the low sHLA-G group. These two variables and mRss were associated with sHLA-G levels at logistic regression analysis. Treatment had no influence on sHLA-G. Moreover, a higher frequency of scleredema was detected in the del + /del + than the del - /del + group ( P = 0.04). These data suggest modulatory effects of sHLA-G on SSc. Prospective studies are needed to investigate a role in predicting the disease course.